Two novel metal–organic coordination polymers based on ligand 1, 4-diazabicyclo[2.2.2]octane N, N′-dioxide with phase transition, and ferroelectric and dielectric properties12. Issue 39 (26th September 2017) - Chen, Lizhuang; Ji, Qin; Wang, Xingang; Pan, Qijian; Cao, Xingxing; Xu, Guancheng
Abstract : The synthesis of two low-temperature structural phase transition compounds [Ag3 (dabcodo)(NO3 )3 ]·H2 O n (1 ) and [Ca(Dabcodo)(H2 O)4 Cl2 ] n (2 ) are described. Compound1 displayed ferroelectric–ferroelectric phase transition. Abstract : Two novel metal–organic complexes [Ag3 (dabcodo)(NO3 )3 ]·H2 O n (1 ) and [Ca(dabcodo)(H2 O)4 Cl2 ] n (2 ) containing metal salt and 1, 4-diazabicyclo[2.2.2]octane N, N ′-dioxide (dabcodo), in which dabcodo is coordinated with two types of metal ions, were successfully synthesized. Differential scanning calorimetry, powder X-ray diffraction, variable-temperature structural analyses, dielectric measurements and rectangular polarization-electric field hysteresis loops revealed that1 underwent phase transition from room-temperature-phase Pca 21 to low-temperature-phase Cc at T t ≈ 217 K, accompanied by remarkable dielectric relaxation. Compound1 was a typical ferroelectric–ferroelectric phase transition material with an electric hysteresis loop showing a remnant polarization ( P r ) of ca. 0.23 μC cm −2 and a coercive field ( E c ) of 6.5 kV cm −1 . Room-temperature and low-temperature phases of1 featured the same topology structure of 3 4 ·4 6 ·5 17 ·6 16 ·7 2 . Compound2 underwent a paraelectric–paraelectric phase transition from room-temperature-phase I 4/ mmm to low-temperature-phase Cmcm at T t ≈ 177 K. Moreover, this study contributes to a deeper understanding of the structure–property relationship in emerging metal–organic ferroelectrics.